2009
DOI: 10.1603/022.038.0202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weather onIps typographus(Coleoptera Curculionidae) Phenology, Voltinism, and Associated Spruce Mortality in the Southeastern Alps

Abstract: Summer drought associated with high temperatures recorded in the last few years has given rise to outbreaks of bark beetles developing in weakened host trees. The aim of this study was to investigate the possible weather effect on the biology of and damage caused by Ips typographus L. in the southeastern Alps. The study was carried out recording temperature (1962-2007), precipitation (1922-2007), and the damage caused by I. typographus (1993-2007). In addition, data from pheromone-baited traps (1996-2005) prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 47 publications
3
88
0
2
Order By: Relevance
“…Recent studies from northern [13] and central Europe [3] report that the availability of breeding substrates and the ability of I. typographus to colonize spruce trees growing in suboptimal conditions are the main abiotic factors triggering I. typographus outbreaks. A number of environmental factors may indirectly affect the population dynamics of I. typographus, acting on the susceptibility of the host trees through severe climate events, e.g., drought, heat waves, wind or snow storms, occurring in sites unsuitable for spruce growing [11,17,19]. In this respect, the warm summer temperature recorded in the last few years in southern Europe [45] became one of the main factors affecting the general health conditions of spruce forests [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies from northern [13] and central Europe [3] report that the availability of breeding substrates and the ability of I. typographus to colonize spruce trees growing in suboptimal conditions are the main abiotic factors triggering I. typographus outbreaks. A number of environmental factors may indirectly affect the population dynamics of I. typographus, acting on the susceptibility of the host trees through severe climate events, e.g., drought, heat waves, wind or snow storms, occurring in sites unsuitable for spruce growing [11,17,19]. In this respect, the warm summer temperature recorded in the last few years in southern Europe [45] became one of the main factors affecting the general health conditions of spruce forests [46].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the warm summer temperature recorded in the last few years in southern Europe [45] became one of the main factors affecting the general health conditions of spruce forests [46]. Long, warm and dry summers may enhance tree susceptibility to forest pests [11,17,19], and I. typographus outbreaks were often associated with these events [11]. In the same region where this study was carried out, Marini et al [19] found an altitudinal distribution of I. typographus damage correlated with summer temperature and insect outbreak dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…flight activity between early May and mid-August (Harding and Ravn, 1985), or the flight period in Central Europe which is even longer, i.e. between April and September (Faccoli andStergulc, 2004, Baier et al, 2007). Such an extended flight period has also been recorded further north, (i.e.…”
Section: Seasonal Flight Patternsmentioning
confidence: 99%